The Effect of Culture on Energy Efficient Vehicle Ownership - Massimo Filippini; Tobias Wekhof (ETH Zurich, CER-ETH - Center of Economic Research, 2017)
Does culture affect consumer preferences for fuel efficient vehicles? Switzerland's citizens share all major institutions but belong to multiple population groups which differ by culture or language across distinct geographical locations. This unique setting allows separation of the effect of culture on institutions and on individual consumer preferences. We set up a spatial fuzzy Regression Discontinuity Design (RDD) at the internal French/German language border to estimate the effect of culture on preferences for energy efficient design and control for local policies. A within-country analysis on the municipality level provides a natural experiment because institutions relevant to economic development are shared by the whole population, whereas culture is heterogeneous. Our results indicate that in French speaking regions of Switzerland the share of energy efficient vehicles is 5.5 percentage points higher than in German speaking regions. In addition, we find that popular votes on environmental issues receive a significantly higher share of approval in the French speaking regions, indicating that they place a higher value on the environment.
Keywords: Q2; Q4; R4; Z10; 330; Culture; Transportation; Energy Efficiency; Spatial RDD; Car Choice